"I Just didn't Think they Would Because of My Status…": Experiences of People with HIV within the Ontario Adoption System. Issue 2 (3rd April 2021) - Underhill, Angela; Kennedy, V. Logan; Lewis, Johanna; Loutfy, Mona
Abstract: There is limited research exploring the experiences of people living with HIV (PLWH) who have pursued/successfully adopted children. We aimed to gain a deeper understanding of such experiences by analyzing six interviews with PLWH using thematic analysis. In this paper, we highlight three themes: Understanding the Adoption Process, Desire for Caseworker-Client Transparency, and Framing Health and Wellbeing. While most of the findings are relevant for all people navigating the adoption system, there are clear complexities in the process due to HIV stigma. We consider the key takeaways and offer recommendations for adoption service providers, governing bodies, and future research.